Mitigating climate change impacts on irrigation water shortage using brackish groundwater and solar energy - Zeinab M. El-Fakharany (Elsevier, 2021)
Increase temperature globally would increase irrigation water requirements. Therefore, brackish groundwater can be used as non-conventional water resources in potential solar areas to supplement irrigation water shortage. Consequently, humidification dehumidification greenhouse agriculture used solar energy to desalinating groundwater. The objective of this research is to mitigate the impacts of climate change on water shortage in Qena, Upper Egypt to supplement water shortage. MODIS data were downloaded to get NDVI and Kc and estimate study area irrigation water requirements. Besides, the groundwater model was constructed using MODFLOW software to study the potentiality of groundwater aquifer for development considered the expected impacts of climate change due to temperature increase in the management scenarios. Also, estimate the required agricultural area to be switched to irrigation by solar desalinating from brackish groundwater in a greenhouse to compensate for water shortage. The results showed an increase in irrigation rate of about 6.78%. Based on the model results, the best management scenario is digging wells with 1.0(km) spacing lifting about 400(m3/day/well) to supply requited irrigation water. For this scenario, the maximum drawdown is about 49(m) after 50(years), which is safe. Results indicated approximately 17.68% of agricultural land could be irrigated using brackish groundwater by humidification dehumidification greenhouse.